Pengaruh Model Pembelajaran Think Talk Write Berbantu Aplikasi Pinterest terhadap Kemampuan Menulis Teks Deskripsi Siswa - Efibora Siboro; Juni Agus Simaremare; Harlen Simanjuntak (AS-SABIQUN, 2026)
This study was motivated by students’ low skills in writing descriptive texts, caused by difficulties in finding and developing ideas, limited collaborative activities, and the suboptimal use of engaging learning media. This study aims to examine the effect of implementing the Think Talk Write learning model combined with the Pinterest application on students’ ability to write descriptive texts. This study used a quantitative approach with a one-group pretest-posttest experimental design, involving 30 seventh-grade students of SMP Negeri 4 Medan selected through cluster random sampling. Data were collected through writing tests at the pretest and posttest stages, which were assessed using a scoring rubric. Data analysis was conducted by calculating the mean and standard deviation, as well as through normality, homogeneity, and hypothesis testing using the t-test at a significance level of 0.05. The results showed an increase in the students’ mean score from 45.16 on the pretest to 80.16 on the posttest. The results of the hypothesis test showed that the calculated t value (10.726) was greater than the t table value (1.6972), so the alternative hypothesis was accepted. This study concludes that the implementation of the Think Talk Write learning model assisted by the Pinterest application has a significant effect on improving students’ ability to write descriptive texts. These findings imply the importance of utilizing innovative technology-based learning models to improve students’ writing skills, activeness, and creativity in Indonesian language learning.